Biomimetic Design of 3D Fibrous Mesh Reinforced Hydrogel Replicating the Form and Function of the Intervertebral Disc. Issue 4 (19th January 2023) - Lu, Changbo; Huang, Xinyi; Yan, Hao; Wang, Ya; Wang, Yibo; Zhuo, Shuyun; Wei, Congying; Qiu, Haiyang; Yang, Xiaojiang; Zhang, Yang; Liu, Mingjie; Lei, Wei
Abstract : While cervical total artificial disc replacement potentially preserves motion of the natural intervertebral disc (IVD), problems also arise involving alterations of the spinal biomechanics. A major challenge lies in restoring mechanics of the natural IVD with appropriate kinematics and biomimetic configuration. A biomimetic artificial IVD model is designed and fabricated using a 3D braided fibrous scaffold and a self‐healable hydrogel matrix. The artificial IVD is characterized by 3D four‐directional fibrous structure resembling natural annulus fibrosus and self‐healable hydrogel‐mimicking natural nucleus pulposus. In the compression tests, the artificial IVD exhibits reasonable mechanical behaviors and desired viscoelastic behaviors similar to the natural IVD. After fatigue loading of 5 million cycles, the artificial IVDs become stiffer, whereas the mechanical values remain within the reasonable range. Finite‐element analysis of the artificial IVD from mesoscale and macroscale analysis indicates the coherent load transfer through both the interconnections within the fiber mesh and the fiber–matrix interface, and the entire IVD shows a stress profilometry similar to natural IVD. In conclusion, a biomimetic prototype of artificial IVD with nature‐mimicking mechanics and structure is fabricated. The presence of interwoven fibrous mesh, hydrogel confinement, and proper interfacial adhesion is all essential for scalable production of the IVD. Abstract : A biomimetic prototype of artificial intervertebral disc with nature‐mimicking mechanics and structure is fabricated. The design possesses an angle‐ply fiber scaffold with multiscale structural hierarchy, which exhibits osmotic behaviors, nonlinear viscoelasticity, and duralibity, enduring it a great potential for total cervical disc replacement in future.